MANAJEMEN PEMBELAJARAN IPA DENGAN MODEL INKUIRI PADA MTsN KEMBANG TANJUNG KABUPATEN PIDIE. - Eva Zulyani, Yusrizal, Khairuddin. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Learning Management is a system of guidance, supervision, maintenance, management, leadership that is carried out in a planned, including several matters, such as learning management, student management, and school-and-community management in various forms of activities for the implementation of education. In educational institutions, teachers became the first person in charge to guide, teach, educate and train students to reach maturity. The purpose of this study was to determine in particular the learning management in science subject by inquiry model to the learning process that includes: (1) planning of science learning program with the inquiry model. (2) Implementation of the learning science by inquiry model. (3) Evaluation of the learning science by inquiry model. This study used a qualitative descriptive methods, and data collection techniques are done by the study of documentation, observation and interviews. The subjects were the principal, science teachers and students at Islamic Junior High School (MTsN) Kembang Tanjong of Pidie regency. The research found that: (1) The planning of learning science program prepared by science teachers before implementing the learning process consists of: the identity of the subjects, the standard of competence, basic competence, indicators of achievement of competencies, learning objectives, learning materials, time allocation, learning sources/ tools and assessment results; (2) Implementation of the learning science by inquiry model for materials of magnetism consists of: starting the class, encouraging active participation of students to conduct experiments, using instructional media,  discussing the results of the experiment and drawing conclusions (3) Evaluation of learning science by inquiry model consists of: assessment in the form of observation of oral and written tests. Keywords: Learning Management and Inquiry ModelAbstrak:Manajemen pembelajaran merupakan suatu sistem pengarahan, pembinaan, pengurusan, ketatalaksanaan, kepemimpinan yang dilakukan secara terencana, yang mencakup beberapa hal di antaranya manajemen pembelajaran, manajemen kesiswaan, manajemen hubungan madrasah dengan masyarakat dalam berbagai bentuk kegiatan untuk proses pelaksanaan pendidikan. Di lembaga pendidikan, guru menjadi orang pertama yang bertugas membimbing, mengajar, mendidik dan melatih siswa untuk mencapai kedewasaan. Tujuan penelitian ini adalah untuk mengetahui secara khusus manajemen pembelajaran IPA dengan model inkuiri dalam proses belajar mengajar yang meliputi: (1) Perencanaan program pembelajaran IPA dengan model inkuiri. (2) Pelaksanaan pembelajaran IPA dengan model inkuiri. (3) Evaluasi program pembelajaran IPA dengan model inkuiri. Penelitian ini menggunakan metode deskriptif  kualitatif, teknik pengumpulan data dilakukan dengan cara studi dokumentasi, observasi dan wawancara. Subjek penelitian ini adalah kepala madrasah, guru IPA dan siswa MTsN  Kembang Tanjung Kabupaten Pidie. Hasil penelitian ditemukan bahwa: (1)Perencanaan program pembelajaran IPA yang dipersiapkan guru IPA sebelum melaksanakan proses belajar mengajar yaitu terdiri dari: identitas mata pelajaran, standar kompetensi, kompetensi dasar, indikator pencapaian kompetensi, tujuan pembelajaran, materi pembelajaran, alokasi waktu, sumber/alat pembelajaran dan penilaian hasil; (2) Pelaksanaan  pembelajaran IPA dengan model inkuiri untuk materi kemagnetan terdiri dari: membuka pelajaran, mendorong partisipasi aktif siswa untuk melakukan percobaan, menggunakan media pembelajaran, mendiskusikan hasil percobaan dan menarik kesimpulan (3) Evaluasi  pembelajaran IPA dengan model inkuiri terdiri dari: penilaian  berupa observasi, tes lisan  dan tulisan.Kata Kunci : Manajemen Pembelajaran dan Model Inkuiri.